Honesty Canteen as a Project-Based Learning Model for Strengthening the Pancasila Student Profile in Elementary Schools - Kinkin Karimah Nursyabani; Yunus Abidin; Yusuf Tri Herlambang; Dinie Anggraeni Dewi (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines the Honesty Canteen program as a project-based learning strategy for strengthening the Pancasila Student Profile in an elementary school. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving 22 participants, including the principal, teachers, canteen managers, students, and a parent representative. Data were analyzed using the Miles, Huberman, and Saldaña interactive model with triangulation to ensure trustworthiness. The findings show that the program was implemented through five interrelated strategies: habituation, role modeling, participatory supervision, reward mechanisms, and values internalization. Quantitative records indicated that students’ honesty rate increased from 51% at the initial phase to 100% after pedagogical interventions such as role-play and collective reflection, with an average of 91%. Qualitative evidence further showed moral internalization through students’ voluntary confession and restitution behaviors. The study concludes that the Honesty Canteen can function as a contextual P5 model that supports integrity, independence, and global diversity in the Pancasila Student Profile.